PENGARUH MARKET VALUE RATIO, LEVERAGE, DAN PROFITABILITAS TERHADAP FUTURE INVESTMENT (Studi Pada Perusahaan Subsektor Asuransi yang Terdaftar di BEI Periode Tahun 2010-2016) - Devita Febriana Damayanti; Siti Ragil Handayani; Ferina Nurlaily (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
The type of research was explanatory research. The population in this study were all insurance sub-companies listed on the Indonesia Stock Exchange Period of 2010 to 2016 and obtained 5 sample companies selected based on certain criteria tailored to the purpose of research. The method used in this research was multiple linear regression analysis. The results of this study proved that: 1)on Investment Rate (a)Book to Market Ratio, Debt Ratio, Return on Equity and Return on Asset have significant effect on Investment Rate; (b)Book to Market Ratio partially has a significant effect on Investment Rate; (c)Debt Ratio partially has no significant effect on Investment Rate; (d) Return on Equity partially has no significant effect on Investment Rate; (e) Return on Asset partially has no significant effect on Investment Rate. 2) on Investment Opportunity (a) Book to Market Ratio, Debt Ratio, Return on Equity and Return on Asset have significant effect on Investment Opportunity; (b)Book to Market Ratio partially has a significant effect on Investment Opportunity; (c) Debt Ratio partially has a significant effect on Investment Opportunity; (d) Return on Equity partially has a significant effect on Investment Opportunity; (e)Return on Assets partially has a significant effect on Investment Opportunity. Kеywords: Investment Rate, Investment Opportunity, Book to Market Ratio, Debt Ratio, Return on Equity and Return on Asset. АBSTRАK Jenis penelitian ini adalah penelitian penjelasan (Explanatory Research). Populasi dalam penelitian ini adalah seluruh perusahaan subsektor asuransi yang terdaftar di Bursa Efek Indonesia Periode tahun 2010-2016 dan didapat 5 perusahaan sampel yang terpilih berdasarkan kriteria tertentu yang disesuaikan dengan tujuan penelitian. Metode yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil penelitian ini membuktikan bahwa : 1) pada Investment Rate (a) Book to Market Ratio, Debt Ratio, Return on Equity dan Return on Asset berpengaruh signifikan terhadap Investment Rate; (b) Book to Market Ratio secara parsial berpengaruh signifikan Investment Rate; (c) Debt Ratio secara parsial tidak berpengaruh signifikan Investment Rate; (d) Return on Equity secara parsial tidak berpengaruh signifikan Investment Rate; (e) Return on Asset secara parsial tidak berpengaruh signifikan Investment Rate. 2) pada Investment Opportunity (a) Book to Market Ratio, Debt Ratio, Return on Equity dan Return on Asset berpengaruh signifikan terhadap Investment Opportunity; (b) Book to Market Ratio secara parsial berpengaruh signifikan Investment Opportunity; (c) Debt Ratio secara parsial berpengaruh signifikan Investment Opportunity; (d) Return on Equity secara parsial berpengaruh signifikan Investment Opportunity; (e) Return on Asset secara parsial berpengaruh signifikan Investment Opportunity. Kаtа Kunci: Investment Rate, Investment Opportunity, Book to Market Ratio, Debt Ratio, Return on Equity dan Return on Asset.